Synthesis, Characterization and Scintillation Response of ZnWO4-GO Nanocomposite - Azadmehr, Sadegh; Jafat Taftreshi, Mjid; Alamdari, Sanaz (Journal of Composites and Compounds, 2022)
Graphene-based oxide nanocomposite materials have been commonly used in various applications due to their novel features. In this study, zinc tungstate /graphene-oxide composite nanoparticles (ZnWO4/GO CNPs) were synthesized by a simple chemical method and their structural and optical properties were investigated. Results from EDX verified the presence of associated elements in the structure. The morphology, particle size and structural parameters were also studied and reported. The prepared composite was in monoclinic wolframite crystalline phase with spherical uniformly morphology and average particle size of 299 nm. Under UV and alpha ray irradiation, the prepared ZnWO4/GO CNPs showed blue-green emissions and strong scintillation sensitivity respectively at room temperature. The results showed that ZnWO4/GO CNPs can be a suitable candidate for a wide range of applications in optoelectronic devices.